2018
DOI: 10.1186/s41155-018-0088-x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived parenting and adolescents’ adjustment

Abstract: Adolescence is an important developmental period that is characterised by heightened problems of adjustment. The aim of this study is to analyse adolescents' adjustment, and to explore the typologies and dimensions of parenting, and thus to determine the relationships between these factors. The sample comprised 1285 adolescent students aged 12 to 16 from the Basque Country (Spain). The students filled out the self-report of the Behavior Assessment System for Children (BASC) and the Parental Acceptance-Rejectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 54 publications
0
23
1
2
Order By: Relevance
“…The present study aimed to explore the influence of parenting practices on the establishment of family socialization style, understood as an emotional context or climate [13] in which parenting practices may acquire different meaning when both the mother’s and father’s affect-communication and strictness are combined. Previous studies have often focused on analyzing the style of a single parent, mainly the mother [22,37], although subsequently the weight of both parents in adolescent socialization and development has been recognized, with some authors studying the effect of each parent’s practices on children’s adjustment or maladjustment separately [24,25,26,41,69].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study aimed to explore the influence of parenting practices on the establishment of family socialization style, understood as an emotional context or climate [13] in which parenting practices may acquire different meaning when both the mother’s and father’s affect-communication and strictness are combined. Previous studies have often focused on analyzing the style of a single parent, mainly the mother [22,37], although subsequently the weight of both parents in adolescent socialization and development has been recognized, with some authors studying the effect of each parent’s practices on children’s adjustment or maladjustment separately [24,25,26,41,69].…”
Section: Discussionmentioning
confidence: 99%
“…One specific element of this would be consistency between parents, which despite being considered vital to children’s adjustment, has received relatively little empirical attention [53]. Indeed, the few previous studies which have been carried out in this field seem to indicate better adjustment among adolescents whose parents have similar parenting styles, characterized by a predominance of affect-communication [22,33,35,84], a finding which is consistent with the results observed here, which suggest that the affect-communication of both parents makes a significant and positive contribution to family style. Nevertheless, it has yet to be confirmed whether consistency between maternal and paternal parenting practices [35,84,85,86] really does foster a family socialization style that is more positive for children’s and young people’s development, and if so, how specifically it contributes to said psycho-social adjustment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research about this concept has obtained less consistent results [32], especially in different cultural contexts [14,16]. Some studies have found that greater parental control is related to adolescents’ better psychological adjustment [32,33,34,35], fewer antisocial and criminal activities [34,36], and a later sexual initiation [37], whereas others find a negative effect related to emotional [36,38,39,40] and behavioral problems [41]. Similarly, some studies have found a positive relationship between parental behavioral control and academic performance in European-American teenagers, but not in African-American ones [33], whereas others have found no association [35] or a negative association [25].…”
Section: Introductionmentioning
confidence: 99%